Rare Case of Community-Acquired Endocarditis Caused by Neisseria meningitidis Assessed by Clinical Metagenomics - Choutko, Vassili; Lazarevic, Vladimir; Gaïa, Nadia; Girard, Myriam; Renzi, Gesuele; Leo, Stefano; Keller, Peter M.; Huber, Christoph; Schrenzel, Jacques (Frontiers in Cardiovascular Medicine, 2019)
The most common causes of infective endocarditis (IE) are Staphylococcus, Streptococcus, Enterococcus and HACEK-related organisms. In 15–30% of the IE cases, standard blood cultures remain sterile. We aimed at identifying the causative agent of a blood-culture-negative IE by whole metagenome shotgun sequencing (WMGS). A 54-year old woman diagnosed with community-onset pneumonia by a general practitioner, was admitted with dyspnea, cough and fever. The patient’s blood cultures were repeatedly negative. The transesophageal echocardiography and transthoracic echocardiography showed an echo density on the left coronary leaflet of the aortic valve and signs suggestive of a ruptured abscess of the mitro-aortic junction. The patient underwent a semi-urgent aortic valve replacement by a mechanical prosthetic valve. We extracted DNA from the surgically-removed fresh valve tissue. The extraction procedure included bacterial/fungal DNA enrichment procedure. Nextera XT library prepared from the valve DNA extract was sequenced (2250) on an Illumina MiSeq instrument. Sequence reads were mapped against bacterial genomic sequences, 16S rRNA genes and clade-specific taxonomic markers. Most of the 103,136 sequencing reads classified as bacterial were assigned to Neisseria meningitidis. In line with these data, mapping of reads against clade-specific and 16S rRNA gene markers revealed N. meningitidis as the most represented species. Assembled metagenomic fragments had the best average nucleotide identity (ANI) with N. meningitidis. Comparison of assembled contigs to reference alleles showed that this strain belongs to the ST-41/44 complex/Lineage 3. N. meningitidis is commonly associated with meningitis and/or septicemia but should not be neglected as a causative agent of IE, which became exceedingly rare with the introduction of antibiotics. Our data show that WMGS may be used as a diagnostic procedure to strengthen the diagnosis of IE and to obtain draft genomic sequence of the pathogen and typing information.